IDENTIFICAÇÃO DE PERDAS NO SERVIÇO DE REVESTIMENTO CERÂMICO EM UMA OBRA PÚBLICA: ESTUDO DE CASO - Lima, Aline; Santos, Débora de Gois; Lima, Renan (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Various reasons can compromise the physical-financial planning of a construction. Some of them can be categorized into the waste classification proposed by the Toyota Production System (TPS) and the waste defined by Koskela (2004) as making-do. In public work, the occurrence of those types of waste is more common. Besides, the problems caused by the bidding process aggravate the situation. The purpose of the study was to identify which types of waste occur during the ceramic cladding execution, in public work, and how they affect the construction cost. The research object was a construction in the city of Nossa Senhora do Socorro, state of Sergipe, where it was been executed, among other services, the internal ceramic cladding. The methodology applied in this work was a case study with qualitative and descriptive documentary research. The results showed that, during the execution of the service analyzed, five TPS wastes occurred, besides the making-do. Examples of rework, unfinished work and failures in the phases of the bidding process were also observed. Through the comparative analysis between the planned and the executed, it is suggested to increase the costs and impacts in the global time.